The Crisis of Expertise? Digital Religious Authority in Islamic Political Discourse on YouTube - Elita Putri Pradipta; Firly Annisa (Universitas Ahmad Dahlan, 2026)
This study examines the transformation of religious authority in digital media through Islamic political discourse on YouTube, focusing on the content produced by Guru Gembul. Employing Fairclough’s Critical Discourse Analysis, this research analyzes selected YouTube videos published between December 2024 and April 2025, using video transcripts and visual elements as primary data. The study investigates how religious authority is discursively constructed in the absence of formal religious or academic credentials. The findings reveal that authority is produced through casual language, emotional appeals, and trend-responsive narratives that prioritize audience engagement over epistemic depth. Rather than presenting systematic theological arguments, book references function as symbolic markers of intellectual credibility. It indicates a shift in how expertise is evaluated in digital religious spaces, where visibility, affectivity, and resonance with audiences become central sources of authority. This study contributes to scholarship on digital religion and media discourse by demonstrating how religious authority is reconfigured through platform-mediated discursive practices, extending Critical Discourse Analysis beyond traditional institutional contexts. In practice, the findings highlight the importance of digital literacy for critically assessing religious authority in online environments.